The Symbolic Violence In “Imperfect” (Pierre Bourdieu's Review of Critical Discourse Analysis) - Yunus Khoirul Amal; Prasetyo Adi Wisnu Wibowo; Titis Srimuda Pitana (Universitas Sebelas Maret, 2022)
The film